New first-order allpass filters employing single modified third generation current conveyor - (:unkn) unknown (My University, 2004)
0

The third generation current conveyor (CCIII) presented by Fabre is shown to be a useful active element to pick up the current of a floating passive element. CCIII can be considered as a current controlled current source with unity gain. The use of controlled sources with unity gain in the design of active-RC filters leads to structures with tight design equations. In order to relieve these, it may be useful to insert a gain larger than unity. The modified third generation current conveyor (MCCIII) is a newly introduced active building block to realize this property and to provide new possibilities in the circuit synthesis. In this paper, four new first-order allpass filter configurations employing a single modified third-generation current conveyor (MCCIII) are presented. To demonstrate the advantages of the proposed circuit topologies, a quadrature oscillator is designed employing the proposed allpass sections. SPICE simulation results verifying theoretical analyses are also included.
Keywords: Mühendislik, Elektrik ve Elektronik